Rehabilitation management of pediatric post-Covid 19 syndrome: A case report - Rizky Kusuma Wardhani; Luh Karunia Wahyuni; Budiati Laksmitasari; Clements Clements; Skolastika Mitzy Benedicta (Faculty of Medicine, Universitas Islam Indonesia, 2022)
Indonesia is one of the countries with highest rate of COVID infection in pediatric population. Although the symptoms of acute COVID infection in children are mostly mild, several studies report frequent post-COVID persisting symptoms in pediatric population, causing limitations in daily activities. This case report discusses rehabilitation therapy in a 12 years old child diagnosed with post-COVID syndrome. Rehabilitation therapy in the form of breathing exercise, muscle strengthening, and aerobics exercise can improve subjective complaints, cardiopulmonary endurance, and quality of life at two weeks follow-up. Further research is needed to determine the correlation between rehabilitation therapy and the outcome of children with post-COVID 19 syndrome.